Governance of Co-operative Societies in Nepal: A Case Study of Makawanpur District - Shilpakar, Ishwari (A Peer Reviewed Journal on Social Sciences, 2024)
This study describes the governance of cooperatives in Nepal with a focus on Makawanpur district. Key governance aspects such as transparency, accountability, member participation and financial management were analyzed. 18 cooperatives were selected from about 300 cooperatives in Makawanpur district through a purposive sampling method. It was found that only 66.6 percent submitted financial transparency reports, 44.4 percent followed accountability rules and 39.0 percent involved members in the decision-making process. Among these facts, accountability and involvement of members in the decision-making process are very weak. Along with political interference and inadequate management, these governance weaknesses put cooperative stability and members’ funding at great risk. Strengthening governance mechanisms is critical to the trust, credibility and long-term success of cooperatives in Nepal. Addressing the issues of transparency, accountability, member engagement, inclusiveness, and financial governance is essential for improving the sustainability and credibility of cooperative societies in Nepal.